Real-Time and Deliberative Decision Making Application to Emerging Stressors - Linkov, Igor; Ferguson, Elizabeth A.; Magar, Victor S. (NATO Science for Peace and Security Series C: Environmental Security, 2008)
Decision-making tools are needed to support environmental management in an increasingly global economy. Addressing threats and identifying actions to mitigate those threats necessitates an understanding of the basic risk assessment paradigm and the tools of risk analysis to assess, interpret, and communicate risks. It also requires modification of the risk paradigm itself to incorporate a complex array of quantitative and qualitative information that shapes the unique political and ecological challenges of different countries and regions around the world. This book builds a foundation to characterize and assess a broad range of human and ecological stressors, and risk management approaches to address those stressors, using chemical risk assessment methods and multi-criteria decision analysis tools. Chapters discuss the current state-of-knowledge with regard to emerging stressors and risk management, focusing on the adequacy of available systematic, quantitative tools to guide vulnerability and threat assessments, evaluate the consequences of different events and responses, and support decision-making. This book opens a dialogue on aspects of risk assessment and decision analysis that apply to real-time (immediate) and deliberative (long-term) risk management processes.